2002
DOI: 10.1007/s00417-002-0478-7
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal ERG in multiple evanescent white dot syndrome

Abstract: Our mf-ERG findings show different results during the course of the disease. First-order kernel amplitudes seem to reflect early disturbances of the photoreceptors in MEWDS and are therefore useful in detecting early stages and following up the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 31 publications
(28 reference statements)
1
19
1
1
Order By: Relevance
“…9). 23,40,58,108,217 Furthermore, mfERG also showed more widespread retinal dysfunction compared with subjective visual field testing. The natural course of mfERG abnormalities in MEWDS have also been studied longitudinally and recovery of mfERG responses to normal level paralleled with resolution of symptoms and clinical findings.…”
Section: Other Acquired Retinopathy Multiple Evanescent White Dot Synmentioning
confidence: 94%
See 2 more Smart Citations
“…9). 23,40,58,108,217 Furthermore, mfERG also showed more widespread retinal dysfunction compared with subjective visual field testing. The natural course of mfERG abnormalities in MEWDS have also been studied longitudinally and recovery of mfERG responses to normal level paralleled with resolution of symptoms and clinical findings.…”
Section: Other Acquired Retinopathy Multiple Evanescent White Dot Synmentioning
confidence: 94%
“…The natural course of mfERG abnormalities in MEWDS have also been studied longitudinally and recovery of mfERG responses to normal level paralleled with resolution of symptoms and clinical findings. 40,58,217 Feigl et al showed that MEWDS patients who presented within seven days of symptoms had supernormal N1 and P1 mfERG amplitudes with normal implicit times. 58 This was followed by decrease in response amplitudes two weeks after onset of symptoms.…”
Section: Other Acquired Retinopathy Multiple Evanescent White Dot Synmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between MFC and MEWDS may indicate a common etiological factor (16) . In these cases, multifocal electroretinogram can help to differentiate MFC from MEWDS, with deep wave depression in MFC and an initial focal loss in MEWDS, followed by full recovery of retinal function at about 7-14 days (24,25) .…”
Section: Discussionmentioning
confidence: 99%
“…Such lesions varied in size from 50 to 500 μm in diameter [42]. Full-field and multifocal electroretinograms disclose dysfunction at the photoreceptors level [43,44]. A typical OCT finding is the disruption of the photoreceptor inner/outer segment junction line which can recover along with the resolution of the disease [45].…”
Section: Multiple Evanescent White Dot Syndromementioning
confidence: 99%